Experimental evidence of ericoid mycorrhizal potential within Serendipitaceae (Sebacinales) - Vohník, Martin; Pánek, Matěj; Fehrer, Judith; Selosse, Marc-André (Mycorrhiza, 2016)
The Sebacinales are a monophyletic group of ubiquitous hymenomycetous mycobionts which form ericoid and orchid mycorrhizae, ecto- and ectendomycorrhizae, and nonspecific root endophytic associations with a wide spectrum of plants. However, due to the complete lack of fungal isolates derived from Ericaceae roots, the Sebacinales ericoid mycorrhizal (ErM) potential has not yet been tested experimentally. Here, we report for the first time isolation of a serendipitoid (formerly Sebacinales Group B) mycobiont from Ericaceae which survived in pure culture for several years. This allowed us to test its ability to form ericoid mycorrhizae with an Ericaceae host in vitro, to describe its development and colonization pattern in host roots over time, and to compare its performance with typical ErM fungi and other serendipitoids derived from non-Ericaceae hosts. Out of ten serendipitoid isolates tested, eight intracellularly colonized Vaccinium hair roots, but only the Ericaceae-derived isolate repeatedly formed typical ericoid mycorrhiza morphologically identical to ericoid mycorrhiza commonly found in naturally colonized Ericaceae, but yet different from ericoid mycorrhiza formed in vitro by the prominent ascomycetous ErM fungus Rhizoscyphus ericae. One Orchidaceae-derived isolate repeatedly formed abundant hyaline intracellular microsclerotia morphologically identical to those occasionally found in naturally colonized Ericaceae, and an isolate of Serendipita (= Piriformospora) indica produced abundant intracellular chlamydospores typical of this species. Our results confirm for the first time experimentally that some Sebacinales can form ericoid mycorrhiza, point to their broad endophytic potential in Ericaceae hosts, and suggest possible ericoid mycorrhizal specificity in Serendipitaceae.
Keywords: Sebacinales; Ericaceae; Endophytes; Ericoid mycorrhiza; Serendipitaceae; Plant Roots; kořeny rostlin; mykorhiza; Basidiomycota; Phylogeny; In vitro re-synthesis; Mycorrhizae; fylogeneze; semenáček; Seedlings